2020
DOI: 10.2147/ott.s265364
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prognostic and Therapeutic Significance of Androgen Receptor in Patients with Gastric Cancer</p>

Abstract: Purpose The clinical studies carried out in the last few decades unequivocally introduced activated androgen receptor (AR) as a pathogenic feature of human malignancies which not only endows cancer cells with survival advantage, but also may be exploited for anticancer interventions. Patients and Methods In this study, we have investigated the expression profile of AR and EMT-related genes in fresh gastric cancer (GC), adjacent nontumor and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Aberrant AR expression is a major factor in the development and progression of gastric cancer 36 . According to epidemiological studies, men and women experience GC at a ratio of approximately 2:1 regardless of the etiology, which is related to how AR affects this disease 37 38,39 . By regulating the expression and protein activity of oncogene and antioncogene, AR can substantially affect the complex mechanism that causes and promotes the occurrence and advancement of GC [40][41][42][43][44][45] (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant AR expression is a major factor in the development and progression of gastric cancer 36 . According to epidemiological studies, men and women experience GC at a ratio of approximately 2:1 regardless of the etiology, which is related to how AR affects this disease 37 38,39 . By regulating the expression and protein activity of oncogene and antioncogene, AR can substantially affect the complex mechanism that causes and promotes the occurrence and advancement of GC [40][41][42][43][44][45] (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer, whose incidence is twice higher in males than in females [123], the AR upregulates the gene that codifies metalloprotease 9 (MMP 9), thus promoting cell invasion [125]. Furthermore, by using the antagonist ENZ, it has been demonstrated how the AR correlates with cell proliferation and survival [123].…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…For these reasons, there is a need to investigate new prognostic markers as well as more successful therapies for severe GC. Different reports have indicated that the incidence of GC is significantly higher in men than in women, with a ratio of 2:1 [123], and this will be similar in 2023 [45]. In the 1990s, Wu and colleagues demonstrated for the first time the significant presence of ARs in GC [124], so later reports have since focused on studying the prognostic and therapeutic role of this receptor in GC.…”
Section: Ar In Gastric Cancermentioning
confidence: 99%
See 2 more Smart Citations